2022
DOI: 10.1590/fst.31121
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the role and mechanism of Allicin in ventricular remodeling through PPARα and PPARγ signaling pathways

Abstract: Online) Methods Culture, identification and grouping of primary cardiomyocytes of neonatal rat Culture of primary neonatal rat cardiomyocytesOne-day-old Wistar suckling rats were obtained. The heart was removed, the big blood vessels and atrium at the bottom of the heart were cut off, the heart tissue was cut into a meat-like

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additionally, the inhibitory effects of allicin on cardiac hypertrophy in rats can also be mediated by the inhibition of apoptosis and the stimulation of angiogenesis [ 95 ]. In cell cultures of cardiomyocyte allicin increase the expression of PPARα, PPARγ, and Bcl-2, and downregulate Bax, Fas, and Fax-L, these effects were induced by Angiotensin II stimulation and suggested that allicin can regulate apoptosis and ventricular remodeling [ 96 ].…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Additionally, the inhibitory effects of allicin on cardiac hypertrophy in rats can also be mediated by the inhibition of apoptosis and the stimulation of angiogenesis [ 95 ]. In cell cultures of cardiomyocyte allicin increase the expression of PPARα, PPARγ, and Bcl-2, and downregulate Bax, Fas, and Fax-L, these effects were induced by Angiotensin II stimulation and suggested that allicin can regulate apoptosis and ventricular remodeling [ 96 ].…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Garlic has a long history of use as a plant for both medicine and food. It has been found to be beneficial in adjuvant treatment of tumors, heart diseases, metabolic diseases, anti-inflammatory and anti-bacterial (Arslaner, 2020;Liu et al, 2022). It has been developed into a variety of products, such as Laba garlic, black garlic, etc (Lishianawati et al, 2022;Setiyoningrum et al, 2021;Gao et al, 2019a).…”
Section: Synthesis Of Hydrogels Based On Nanocellulose From Garlic St...mentioning
confidence: 99%
“…Garlic, renowned for its intriguing nature, has been utilized both as a culinary ingredient and for medicinal purposes. It is recognized as being valuable in tumor treatments, metabolic diseases, heart diseases, and it has anti-bacterial, and anti-inflammatory properties [ 33 , 34 ]. In the garlic cultivation sector, garlic straws and peels are well recognized as waste; simply, small amounts are used as food and most are cooked [ 35 ].…”
Section: Introductionmentioning
confidence: 99%